(untitled) (Cadernos de Ética e Filosofia Política, 2022)
In spite of their disagreements, Constant and Hegel agree that modem politics breaks with classical politics since modem freedom makes itself effective only with the mediation introduced by the market or by the State. I shall argue that 1) this common argumentation originates in modem interpretation of politics as the realm in which moral consciousness obtains its public expression. 2) what ensure this process is the teleological approach first developed by Kant. Considering that the nexus betweeen modernity and morality was reinterpreted when teleology turned in crises, I follow general aspects of positive sociology and theory of discourse with the purpose to point out some intrinsic difficulties these two paradigms carry with them.